RELATIONSHIP BETWEEN ENVIRONMENTAL FRAGILITY, SURFACE WATER QUALITY, AND PERMANENT PRESERVATION AREAS IN SAN DOMINGOS STREAM, TRÊS LAGOAS-MS - Brito, Rafael Martins; Garcia, Patrícia Helena Mirandola; Barros, Matheus Henrique de Souza (Geosaberes; Vol 11 (2020): Vol 11 (2020)DO - 10.26895/geosaberes.v11i0.793, 2020)
The dynamics of changes in land use and coverage and other anthropogenic actions lead to the need for an integrated understanding of the environment. The objective of this research is the construction of systemic analysis and the understanding of the relation between the natural elements. For this study, we use a synthetic map of environmental fragility, and the quality of surface water and permanent preservation areas (PPAs) are analyzed. The watershed presents mostly medium environmental fragility (74,85%). The classes of surface waters detected were Class I and Class II, with a lower presence of natural vegetation in PPAs related to Class II. We conclude that areas with silvicultural planting tend to provide higher soil protection against rainwater action, effectively avoiding erosion problems in relation to pasture areas without adequate management.